Efecto de la temperatura de incubación en la determinación del sexo en aves de producción (2024)
Poultry farming, as an essential pillar in the agro industrial sector, faces a range of challenges that bring together genetics, developmental biology and environmental factors. At the center of these challenges is the impact of incubation temperature on sex determination and phenotypic development of birds, a topic of high scientific and practical interest. This literature review focuses specifically on this aspect, considering its relevance in the framework of modern poultry farming, determining an incubation temperature that can significantly influence chick quality, viability and the sex ratio at birth, phenotypic characteristics. key for poultry production. The most important modifiable environmental factor in incubation is temperature; but the strength of this influence depends on the time frame used and the duration of changes in incubation temperature during embryogenesis. This phenomenon is particularly relevant in birds, where females have a heterogametic sexual chromosome configuration and males have a homogametic sexual chromosome configuration. Research has revealed that short-term thermal stimulation, applied in the final days of incubation, appears to increase the proportion of male chicks, a finding that challenges traditional understanding of sex determination in birds.